2006
DOI: 10.1002/qsar.200640050
|View full text |Cite
|
Sign up to set email alerts
|

Developing New Cleavage Strategies in a Fluorous Phase Pummerer Cyclative‐Capture Approach for the Synthesis of N‐Heterocycles

Abstract: An efficient, oxidative cleavage of a sulfur linker has been developed for the fluorous phase synthesis of N-heterocycles. The new cleavage strategy facilitates the synthesis of products containing diverse structural features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…In their studies on fluorous synthesis using a sulfur linker, Procter et al. developed an oxidative tag cleavage–modification protocol that is complementary to the samarium(II) iodide reductive cleavage (see Scheme , Scheme , and Scheme ) 35. Thus, treatment of tagged oxindoles such as 80 with ceric(IV) ammonium nitrate (CAN) resulted in a Pummerer reaction to provide isatins such as 81 in excellent yields.…”
Section: Pummerer Reactions Using An Alternative Methods Of Thioniumentioning
confidence: 99%
“…In their studies on fluorous synthesis using a sulfur linker, Procter et al. developed an oxidative tag cleavage–modification protocol that is complementary to the samarium(II) iodide reductive cleavage (see Scheme , Scheme , and Scheme ) 35. Thus, treatment of tagged oxindoles such as 80 with ceric(IV) ammonium nitrate (CAN) resulted in a Pummerer reaction to provide isatins such as 81 in excellent yields.…”
Section: Pummerer Reactions Using An Alternative Methods Of Thioniumentioning
confidence: 99%
“…We subsequently found that the Pummerer, oxidative cleavage of 7 could be carried out in a single step with ceric(iv) ammonium nitrate ( 6 , CAN), giving 20 in quantitative yield (Scheme 2). [20] The oxidative removal of the fluorous tag worked well for a range of tagged oxindoles (Figure 1), giving the expected 1,2-dicarbonyl products in high yield after purification with FSPE. Interestingly, in the reaction of benzazepinone 15 with CAN, the fluorous tag can be removed in the presence of the PMB protecting group to give dihydrobenzazepine-1,2-dione 21 ( Figure 1).…”
Section: Introductionmentioning
confidence: 95%
“…[31] [35] In diesem Fall führte die Behandlung markierter Oxindole wie 80 mit Cer(IV)-ammoniumnitrat (CAN) zu einer Pummerer-Reaktion, bei der Isatine wie 81 -nützliche Intermediate zum Aufbau vielfältiger Strukturenin hervorragenden Ausbeuten gebildet wurden (Schema 26).…”
Section: Pummerer-reaktionen In Der Synthese Von Thiound Selenonucleounclassified